2007
DOI: 10.1152/ajpheart.01314.2006
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to myofibrillar protein function in nonischemic regions of the heart early after myocardial infarction

Abstract: zone left ventricular dysfunction (LVD) contributes to global reductions in contractile function after localized myocardial infarction (MI). However, the molecular mechanisms underlying this form of LVD are not clear. This study tested the hypothesis that myofibrillar protein function is directly affected in remote-zone LVD early after MI. Cardiac myosin and native thin filaments were purified from mouse myocardium taken from both the nonnecrotic zone adjacent to and the nonischemic zone remote from an infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…Further, Tm phosphorylation increases 150% over control during remote zone left ventricular dysfunction (RZLVD), a contractile disorder that occurs after myocardial infarction, but in regions of the left ventricle that do not experience ischemia. This increase in phosphorylation coincides with a small but significant increase in the velocity of purified thin filaments over myosin in the in vitro motility assay [Rao et al, 2007]. Taken together, these results suggest that Tm phosphorylation may serve as a compensatory mechanism that attempts to upregulate contractile function when myosin activity is significantly reduced.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Further, Tm phosphorylation increases 150% over control during remote zone left ventricular dysfunction (RZLVD), a contractile disorder that occurs after myocardial infarction, but in regions of the left ventricle that do not experience ischemia. This increase in phosphorylation coincides with a small but significant increase in the velocity of purified thin filaments over myosin in the in vitro motility assay [Rao et al, 2007]. Taken together, these results suggest that Tm phosphorylation may serve as a compensatory mechanism that attempts to upregulate contractile function when myosin activity is significantly reduced.…”
Section: Discussionmentioning
confidence: 64%
“…In vitro motility was performed at 30°C at 1 mM ATP as previously described [Guo and Guilford, 2004; Rao et al, 2007; Snook et al, 2008]. In brief, HMM in actin buffer (25 mM KCl, 25 mM Imidazole, 1 mM EGTA, 4 mM MgCl 2 , 10 mM DTT, pH 7.4) was flowed into a flow cell constructed from a nitrocellulose coverslip and glass slide spaced by two mylar shims.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the ATP content was maintained constant in this experimental system, implicating that the contractile dysfunction was due to oxidative damage to sarcomeric proteins and not to a reduction in energy availability. Rao et al [46] showed that I/R increased oxidative stress even in the remote areas of the heart and that cardiac myosin isolated from distal myocardium was less efficient in propelling thin filaments purified from either I/R or control mouse hearts. Both filament sliding velocity and actin-myosin binding were impaired, suggesting that posttranslational modifications of myosin play a role in the pathology of remote-zone left ventricular dysfunction.…”
Section: Oxidative Damage Impairs Contractile Functionmentioning
confidence: 99%
“…After MI, hypertrophy of surviving cardiomyocytes combined with other remodeling effects in non-myocytes initiates the progression to clinical heart failure. Ventricular cells, including those unaffected by ischemia during the MI itself, may display altered or impaired function, a situation sometimes called “remote zone ventricular dysfunction” [1]. The physiology of the myocardium shortly after infarction when the heart has yet to begin maladaptive remodeling is therefore a clinically significant target of investigation.…”
Section: Introductionmentioning
confidence: 99%